PREVALENCE OF IRON DEFICIENCY ANAEMIA IN YOUNG ADOLESCENT GIRLS AT UNIVERSITY OF PESHAWAR - Ghaffar, Fazia; Waqar, Falahat (Pakistan Journal of Physiology, 2018)
Background: Anaemia is one of the most frequent and important health problems among the adolescent girls throughout the world. Iron deficiency anaemia constitutes major anaemia due to rapid growth, hormonal changes, menarche, and malnutrition due to poor dietary intakes. The current study was designed to investigate the role of dietary intake patterns in prevalence of anaemia among the teenage girls residing in hostels. Methods: A convenient random sample of 237 college/undergraduate students residing at girls’ hostels was subjected to anthropometry, biochemical tests for blood iron indices, and dietary intake analysis. Results: Normal mean anthropometric measurements were observed among the sampled students. Sixty-one percent (61%) of girls had haemoglobin (Hb) level below normal, 85% had low haematocrit percent and 82% had low serum iron. The highest category of sub normal Hb level was in the range of 9–11.9 g/dl (48%), haematocrit 25–29.9% (52%), and Serum iron 26–35 µg/dl (34%). The daily dietary intake pattern showed good breakfast consumption (82%), snacking on fried and starchy foods and carbonated beverages a common practice, and skipping of major meals a regular feature. Cereals and grains based diets and lack of fresh fruits and vegetables were found to be contributing factors to the gross prevalence of anaemia among this age group. Conclusion: Anaemia is the most prevalent dietary deficiency disorder among undergraduate students mainly caused by poor dietary intake patterns.